Macromol. Rapid Commun. 1/2017. Issue 1 (3rd January 2017) - Giustina, Gioia Della; Giulitti, Stefano; Brigo, Laura; Zanatta, Michele; Tromayer, Maximilian; Liska, Robert; Elvassore, Nicola; Brusatin, Giovanna
Abstract : Front Cover: 2D and 3D light‐triggered modulation of hydrogel stiffness is described. UV lithography and 3D two‐photon direct laser writing technology afford to alter hydrogel crosslinking degree in two and three dimensions, exploiting a specific chemistry design. Spatially controlled changes in hydrogel mechanical properties induce a biological response: elongated cells and higher proliferation are evident on 2D stiff patterns compared to the less cross‐linked soft regions. Further details can be found in the article by G. Della Giustina, S. Giulitti, L. Brigo, M. Zanatta, M. Tromayer, R. Liska, N. Elvassore, and G. Brusatin* on page 1600570.